ANALISIS PENGARUH PDB, EKSPOR PERTANIAN, SUKU BUNGA DAN INFLASI TERHADAP INVESTASI PMDN PADA SEKTOR PERTANIAN DI INDONESIA TAHUN 2010-2019 - Bambang Priadi; Devi Andriyani (Jurnal Ekonomi Pertanian Unimal, 2021)
This study examined and analyzed the effect of GDP, Agricultural Exports, Interest Rates, and Inflation on domestic investment in the agricultural sector in Indonesia. This study used time-series data from 2010 to 2019. The analytical model used was the Multiple Linear Regression Model. The results partially showed that GDP positively and significantly influenced investment in the agricultural sector in Indonesia. Meanwhile, Agricultural Exports, Interest Rates, and Inflation had no significant and negative effect on investment in the agricultural sector in Indonesia. Simultaneously, GDP, Agricultural Exports, Interest Rates, and Inflation positively and significantly influenced investment in the agricultural sector in Indonesia.